Addressing malnutrition and food insecurity with breadfruit in a rural, developing country: a case study and lessons learned in Thomassique, Haiti - John M Klyver; Inga Haugen; Logan Schulz; Wiscard-Kardin LaPais; Charles Saint-Fleur; Samuel J Starke; Jason Piersaint; Anael S Rizzo; Kyra M Sarazen; Medical Missionaries (Inishmore Laser Scientific Publishing Ltd, 2022)
Haiti's Central Plateau region suffers from significant malnutrition, economic hardship, and a crisis level of food insecurity. Already the poorest country in the Western Hemisphere in terms of gross domestic product (GDP) per capita, Haiti has pervasively high malnutrition rates, but the Central Plateau is among the most severely affected areas. One in five children of the Central Plateau suffers from malnutrition, and the region exhibits a devastating 30% rate of child stunting. Our US-based team affiliated with Klinik Sen Jozèf, a community-respected medical clinic in the Central Plateau city of Thomassique. We partnered with local Haitian leadership, a local agronomist, and Trees That Feed Foundation to introduce breadfruit (*Artocarpus altilis*) and an innovative development model to combat local malnutrition. Five years into the program, we have partnered with 152 farmers, and we have enhanced our malnutrition program with breadfruit derivatives. This report addresses the lessons we learned to assist others looking to introduce models or crops in a similar manner. Our experience is particularly significant in light of the COVID-19 pandemic, as supply chain disruptions have worsened food insecurity for more than 800 million people in low-income countries.